Democratic Republic of the Congo : Interim Poverty Reduction Strategy Paper Preparation Status Report. (IMF Staff Country Reports; Country Report ;, 2003)
In this paper, the implementation of the activities under the interim poverty reduction strategy and progress toward the elaboration of poverty reduction strategy are described. Institutional framework is strengthened by the creation of the inter-ministerial committee on the implementation of the National Strategy for Poverty Reduction. The goal is to identify priorities and strategies at the community level, and their capacity to operationalize sectoral and thematic poverty reduction strategies. The macroeconomic and financial situation has been stabilized. The poverty reduction strategy budget has been prepared on the basis of detailed cost estimates for each task.